The 18-year risk of cancer, angioedema, insomnia, depression, and erectile dysfunction in association with antihypertensive drugs: post-trial analyses from ALLHAT–Medicare linked data - Du, Xianglin L.; Martinez, Journey; Yamal, Jose-Miguel; Simpson, Lara M.; Davis, Barry R. (Frontiers in Cardiovascular Medicine, 2023)
Purpose This study aimed to determine the 18-year risk of cancer, angioedema, insomnia, depression, and erectile dysfunction in association with antihypertensive drug use. Methods This is a post-trial passive follow-up study of Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attack Trial (ALLHAT) participants between 1994 and 1998 that was conducted by linking their follow-up data with Medicare claims data until 2017 of subjects who were free of outcomes at baseline on 1 January 1999. The main outcomes were the occurrence of cancer (among n = 17,332), angioedema (among n = 17,340), insomnia (among n = 17,340), depression (among n = 17,330), and erectile dysfunction (among n = 7,444 men) over 18 years of follow-up. Results The 18-year cumulative incidence rate of cancer other than non-melanoma skin cancer from Medicare inpatient claims was 23.9% for chlorthalidone, 23.4% for amlodipine, and 25.3% for lisinopril. There were no statistically significant differences in the 18-year risk of cancer, depression, and erectile dysfunction among the three drugs based on the adjusted hazard ratios. The adjusted 18-year risk of angioedema was elevated in those receiving lisinopril than in those receiving amlodipine (hazard ratio: 1.63, 95% CI: 1.14–2.33) or in those receiving chlorthalidone (1.33, 1.00–1.79), whereas the adjusted 18-year risk of insomnia was statistically significantly decreased in those receiving lisinopril than in those receiving amlodipine (0.90, 0.81–1.00). Conclusions The 18-year risk of angioedema was significantly higher in patients receiving lisinopril than in those receiving amlodipine or chlorthalidone; the risk of insomnia was significantly lower in patients receiving lisinopril than in those receiving amlodipine; and the risk of cancer, depression, and erectile dysfunction (in men) was not statistically significantly different among the three drug groups.